Antibiofilm activity of secondary metabolites of sponge-associated bacterium Alcanivorax sp. from the Red Sea - Jamal, Mamdoh T.; Satheesh, Sathianeson (Frontiers in Marine Science, 2022)
Sponge-associated bacteria are a well-known source of unique and diverse natural products with potential biological activities. In this study, a rarely occurring sponge-associated bacterium from the genus Alcanivorax was isolated from the sponge Siphonochalina siphonella and subjected to extraction of metabolites. Metabolites were extracted from the culture supernatant and biomass of the bacterium using the solvent extraction method. Extracts were evaluated for antibacterial and antibiofilm activities against five different biofilm-forming bacteria isolated from the microfouling assemblage. The crude extracts were subjected to chemical profiling to identify their composition using gas chromatography-coupled mass spectrometry (GC-MS). The results obtained show mild to strong antibacterial activity of the extracts against the biofilm-forming bacteria with the minimum inhibitory concentration (MIC) of 3.125 mg ml-1. The percentage inhibition of biofilm formation ranged from 46% to 71%. Compounds detected in GC-MS analysis are mostly fatty acids and their derivatives that include compounds with known antibiofilm activity such as tetradecanoic acid, dodecanoic acid, and hexadecanol from the culture supernatant extract. Eicosane; hexadecanoic acid, methyl ester; and hexadecanoic acid, ethyl ester were detected from the biomass extract. Molecular docking analysis of the compounds from the bacterial extracts confirms their potential antibiofilm properties. The result indicated that Alcanivorax sp. associated with the sponge possess relevant antibiofilm activity and may serve as a novel source of secondary metabolites with the application as antibiofilm agents.